Use of healthcare information and advice among non-urgent patients visiting emergency department or primary care. Issue 12 (21st September 2011) - Backman, Ann-Sofie; Lagerlund, Magdalena; Svensson, Tobias; Blomqvist, Paul; Adami, Johanna
Abstract : Background: Healthcare information provided by telephone service and internet sources is growing but has not been shown to reduce inappropriate emergency department (ED) visits. Objective: To describe the use of advice or healthcare information among patients with non-urgent illnesses seeking care before attendance at an ED, or primary care (PC) centres in an urban region in Sweden. Design: Patients with non-urgent illnesses seeking care at an ED or patients attending the PC were followed up with a combination of patient interviews, a questionnaire to the treating physician and a prospective follow-up of healthcare use through a population-based registry. Results: Half of the non-urgent patients attending the ED had used healthcare information or advice before the visit, mainly from a healthcare professional source. In PC, men were more likely to have used information or advice compared with women (OR 2.5 95% CI 1.3 to 5.0), whereas the situation was reversed among ED patients (OR=0.4 95% CI 0.2 to 0.9). Men with no previous healthcare experience attending the ED had the lowest use of healthcare information (p<0.01). Very few in both groups had utilised healthcare information on the internet in a case of perceived emergency. Conclusion: ED patients rated as non-urgent by the triage nurse used more advice and healthcare information than PC patients, irrespective of the physician-rated urgency of the symptoms. The problem seems not to be lack of information about appropriate ED use, but to find ways to direct the information to the right target group.